Examining the Impact of Personality Type, Professional Skepticism, and Ethic on Audit Quality: The Moderating Role of Auditor Experience - Pradhono, Gebyar; Setijaningsih, Herlin Tundjung (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the influence of personality type, professional skepticism, and auditor ethics on audit quality, with auditor experience as a moderating. The study utilizes a quantitative methodology, targeting auditors from public accounting firms in Central Jakarta, Indonesia as the research population, employing purposive sampling as the sampling method. Data collection was accomplished through surveys utilizing a questionnaire, with data analysis performed using SEM-PLS. the findings of this study reveal that personality type, professional skepticism, ethics, and auditor experience significantly impact audit quality. The effects of ethics, professional skepticism, and personality type on audit quality are moderated by auditor experience. Future research could delve deeper into exploring additional factors or moderators, thus providing a more comprehensive understanding of audit quality determinants in different contexts. Firms may consider incorporating personality assessments and ethics training into their hiring processes to ensure the selection of auditors with traits conducive to high-quality audits. The research deomonstrates that auditor experience plays a significant moderating role in shaping the impact of personality type, professional skepticism, and ethics on audit quality